2020
DOI: 10.1007/s10143-020-01383-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary decompressive craniectomy in poor-grade aneurysmal subarachnoid hemorrhage: long-term outcome in a single-center study and systematic review of literature

Abstract: Primary decompressive craniectomy (PDC) in patients with poor-grade aneurysmal subarachnoid hemorrhage (aSAH) in order to decrease elevated intracranial pressure (ICP) is controversially discussed. The aim of this study was to analyze the effect of PDC on long-term clinical outcome in these patients in a single-center cohort and to perform a systematic review of literature. Eighty-seven consecutive poor-grade SAH patients (World Federation of Neurosurgical Societies (WFNS) grades IV and V) were analyzed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Therefore, most relevant studies have been retrospective after performance of DC in poor-grade patients. Although the group with DC had lower mortality and morbidity compared to the group without DC, the group with DC showed higher mortality and morbidity compared to the "good" grade group [5,17]. Previous studies have shown that DC can reduce mortality without sig- grade patients, but the results were inconsistent [3,9,19].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, most relevant studies have been retrospective after performance of DC in poor-grade patients. Although the group with DC had lower mortality and morbidity compared to the group without DC, the group with DC showed higher mortality and morbidity compared to the "good" grade group [5,17]. Previous studies have shown that DC can reduce mortality without sig- grade patients, but the results were inconsistent [3,9,19].…”
Section: Discussionmentioning
confidence: 87%
“…There was no difference in mRS at the time of admission between the 2 groups, but the functional outcomes (mRS) at discharge were better in the group in which clipping was performed. While mortality was not significantly different between clipping and coiling groups, the clipping group showed a nificantly improving functional outcomes [1,4,5,6,17]. Attempting to clip a cerebral aneurysm in a patient with severe brain swelling can cause additional damage to the brain tissue surrounding the cerebral aneurysm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most published series of DHC after SAH report a lower rate of unfavorable outcome after early DHC [ 2 , 12 ]. Early identification of patients with high risk of ICP decompensation is therefore mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size/power calculation is based on a retrospective single-center study and literature review [ 14 ].…”
Section: Interventionsmentioning
confidence: 99%